Kenya : Poverty Reduction Strategy Papers; 2003/2004 and 2004/2005; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents a Joint Staff Advisory Note on Kenya's Poverty Reduction Strategy Papers. Kenya is implementing the three-tiered East Africa Community (EAC) common external tariff and needs to develop a trade strategy, in agreement with other EAC members, that further lowers trade barriers against the rest of the world. As the government works toward meeting the remaining benchmarks, steps should be taken to consolidate public financial management reforms along with regular reviews of the existing plans to better prioritize, coordinate, and monitor reform measures.